Obese hypoventilation syndrome. Presentation of a case - Luis Virgilio Díaz Martìnez; Yenisel Chang Cuesta; Inti Santana Carballosa (Medisur)
Obesity has become an important cause of comorbidities, it is important to recognize the diseases associated with this condition early, as well as its treatment. Obese hypoventilation syndrome, also called Pickwick syndrome, has been defined by the triad of obesity, daytime hypoventilation and altered breathing during sleep, in the absence of another disease that explains the respiratory alterations. The case of a 53-years-old patient, white skin color, male, from urban origin, with a personal pathological history of high blood pressure, gouty arthritis, morbid obesity, unstable angina pectoris, previous episodes of atrial fibrillation and Pickwick syndrome without treatment for it, it is presented. On February the 12th, 2023, he was brought by his family to the Dr. Gustavo Aldereguía Lima Hospital in the Cienfuegos province, because he had had difficulty breathing, a fever of 39ºC, for seven days, and the day before he had begun to expectorate blood. The performed procedures and treatments for each complication are described, until his death. Due to the importance of diagnosis, control and follow-up of these obese patients with comorbidities, to avoid fatal outcomes, it was decided to present the case.